Senegalia ajaya (Mimosoid clade, Caesalpinioideae, Fabaceae), a new species from Birbhum District, West Bengal, India - Alam, Shamim; Lokho, Adani (Phytotaxa, 2024)
A new species of Senegalia, S. ajaya (Mimosoid clade, Caesalpinioideae, Fabaceae) is described and illustrated from Birbhum district of West Bengal, India. This species is closely related to Senegalia caesia but can be distinguished from S. caesia by its distinctive characters such as: climbing shrub habit; internode bearing 6-lines of prickles; tendrils on the branches; rachilla prickles on the underside; two types of paraphyllidia at pinnae bases; asymmetrically rounded leaflet base; mid vein extended straight to the apiculate apex.